Занимательная ботаника для малышей - Лаврова Светлана Аркадьевна (Моя первая книга, 2007)
Экземпляры: ф. 8 (20081013) / Инвентарный номер: 42535 / Цена: 147.51 / Авт.знак: Л 13 / ГРНТИ: 34.29 / ББК: 28.5